Percutaneous closure of the aortic valve as a bridge to heart transplantation to treat severe aortic insufficiency after ventricular assist device. Issue 2 (10th July 2014) - Sauer, Andrew J.; Davidson, Charles J.; McGee, Edwin C.
Abstract : Aortic insufficiency (AI) following rotary left ventricular assist device (LVAD) implantation is an increasingly common problem with inadequately defined treatment options. Percutaneous transcatheter (PTC) closure of the aortic valve (AV) has been described as a potential nonsurgical approach. Alternatively, we present a case of decompensated heart failure due to de novo severe AI following LVAD in which successful PTC closure of the AV resolved the severe AI and allowed for clinical recovery and stability for more than 10 months as a bridge to heart transplantation. © 2014 Wiley Periodicals, Inc.